Enshittification : why everything suddenly got worse and what to do about it - Doctorow, Cory (MCD, Farrar, Straus and Giroux, 2025)
"A book explaining the process of "enshittification"-a term coined by Cory Doctorow to describe the inevitable process of digital platforms getting worse and worse for users, with wide-ranging implications-and how to combat it"-- Provided by publisher.